When Inflation Drives Twin Deficits Catch in the Eurozone - Barbara Brixova; Veronika Šuliková; Marianna Siničáková; Valéria Levandovská (Amfiteatru Economic)
The paper explores the impact of inflation on the validity of the twin deficits hypothesis (TDH) in the Eurozone countries, focussing on how different inflation levels influence twin deficit existence (i.e., a positive relation between fiscal and current account deficit) and how inflation affects current account balance in different inflation intervals. Despite extensive existing research on twin deficits, the specific role of inflation in twin deficits remains underexplored. Using Granger causality tests, cross-correlations, and panel data models, we tested the twin deficit hypothesis at varying inflation levels. According to our findings, if inflation exceeds 2%, the TDH holds. On the contrary, during periods of lower inflation (below 0% or between 0% and 1.7%), the TDH is either invalid or current account is unaffected by inflation. These results highlight the importance of targeted fiscal consolidation during high inflation periods to prevent further current account deterioration. By examining the link between inflation and twin deficits, this study not only addresses a key gap in the literature on twin deficits but also lays the groundwork for future investigations into the complex interplay between inflation and macroeconomic imbalances in the Eurozone.